Sub-Seasonal Variability of Meridional Activity of Western Pacific Subtropical High in Boreal Late Summer - Qian, Qiwen; Liang, Ping; Qi, Li; Ding, Yihui; He, Jinhai (Frontiers in Earth Science, 2020)
Sub-seasonal variability in meridional activity of Western Pacific subtropical high (WPSH) exerts important influences on anomalous weather and climate in East Asian monsoon region. By using a sub-seasonal meridional index of the WPSH, the characteristics and atmospheric evolutions in association with the sub-seasonal meridional activity of the WPSH during boreal late summer are further investigated. The meridional activity of the WPSH exhibits distinctive low frequency oscillation (LFO), with two dominant periods of 10-30 days and 40-50 days. The 10-30 day LFO is influenced by wave trains in mid-high latitudes and convection propagating from tropic. For the northward advance of the WPSH, in the high latitudes, teleconnection wave train originating from Atlantic Ocean propagates eastward, then the positive and negative potential vortex anomalies enhance the high-level divergence in Northeast Asia. In the mid-latitudes, the 10-30 day low frequency wave train from North America propagates westward and influences the pressure field along the East Asia coast, whose energy is gained from the westerly jet through barotropic process. In the tropic, on time scale of 10-30 days, anomalous convections over the equatorial western Pacific propagate northwestward and trigger cyclone-anticyclone circulation anomalies along the East Asia coast, which in turn affect the meridional position of the WPSH. The 40-50 day LFO of meridional activity of WPSH is closely related to the convection anomalies under the interaction between MJO (Madden-Julian Oscillation) and MISO (monsoon intra-seasonal oscillation). The tropical MJO propagates eastward from the equatorial Indian Ocean to West Pacific and then propagates northward, in accompany with the northeastward propagation of anomalous convection teleconnection covering the tropical Indian Ocean-North Indian Peninsula-Northwest Pacific, resulting in the anomalous anti-cyclonic circulation over Northwest Pacific, which contributes to the northward advance of the WPSH. For the southward retreat of the WPSH, the contrary is the case in 10-30 day atmospheric LFO while relatively weaker 40-50 day atmospheric LFO does less contribution to the southward retreat of the WPSH.